Polyvinyl Alcohol-Cellulose Nanocrystal Hydrogel Containing Anti-inflammatory Agent - Lia Amelia Tresna Wulan Asri; Athiya Anindya; Yuni Eva Kartika; Dita Puspitasari; Untung Triadhi; Husaini Ardy (Indonesian Journal of Chemistry, 2022)
Hydrogel wound dressings were developed through cross-linking reactions of polyvinyl alcohol (PVA) with glutaraldehyde and by the addition of diclofenac sodium and rutin as anti-inflammatory agents. Cellulose nanocrystals (CNC) were added to improve mechanically and release properties. CNC was isolated from pineapple leaf fibers through the ammonium persulfate method resulting in a mixture of rod-like whisker and spherical morphology. The mechanical properties of hydrogels are increasing with the addition of CNC. Hydrogels containing 8% CNC exhibited 7.266 N/mm2 tensile strength, 156.3% maximum strain, and 700.3 N/mm2 elastic modulus. Drug release tests containing sodium diclofenac were done by taking incubated phosphate buffer saline samples in a pH 7.4 environment and showed that all CNC variations tested are controllable for the first 30 min compared to the sample without CNC. Sodium diclofenac is easily eluted from hydrogel due to its polar properties, and all samples almost demonstrated the same release profile. PVA hydrogels showed fluctuating concentrations of diclofenac compared to others. While hydrogels containing rutin showed a controlled release mode, the addition of CNC in PVA resulted in a slower release of rutin, possibly due to the better binding between CNC and rutin. To conclude, CNC has successfully improved the performance of PVA hydrogels, including the drug release properties.